Case Series; Respiratory Paralysis Responding to Vitamin D Therapy - Haq Dad Durrani, Sairah Sadaf, Alina Zafar, Rafia Kousar (Pakistan Journal of Medical & Health Sciences, 2023)
Acute ascending flaccid paralysis with areflexia were considered as Guillain-Barre Syndrome by medicine and neurology department as tradition. We present two patients 46 years old female and 57 years old male with acute ascending flaccid paralysis admitted in intensive care unit. They developed respiratory paralysis requiring mechanical ventilation. The male patient developed cardiopulmonary arrest during shifting to intensive care unit. Both the patients responded to vitamin d therapy dramatically. Respiratory paralysis on mechanical ventilation responding to vitamin d therapy dramatically were unique events. Vitamin d deficiency is a worldwide problem but its presentation as acute ascending paralysis with areflexia requiring mechanical ventilation is not cited in medical literature. Keywords; Acute ascending flaccid paralysis with areflexia, Respiratory paralysis, Vitamin D deficiency, Vitamin D therapy,